Book Review: Adancing The Legal Status Of Women In Islamic Law Mona Samadi, Brill Publications, Leiden-&-Boston 2021, 222 P. ISBN: 978-90-04-44693-9 - M. Farooq; Abuhuraiyrah F. Khan (USIM Press, 2024)
Malaysian Journal of Syariah and Law Volume 11 Issue 1 Page (176-179)